The Role of Print Media in Mitigation of Flood Disaster on Public Awareness in Makassar City - Pramudita Budi Rahayu (Journal of Communication Sciences (JCoS), 2018)
One of the roles of local print mass media is to educating society. Which is to inform people about flood disaster in the relevance of effort to bring people to their senses. This research objective is to find out the role of local print mass media in flooded disaster mitigation before and after flooded disaster period. The research took the data from January 2012 until July 2013 edition of Fajar and Tribun Timur newspaper. Method of collecting data is using a coding sheet. Data analyzing is using descriptive quantitative method and content analyze method. The result of this research indicate that on the period before flooding disaster, mass media have a contribute for helping people back to their sense by the news that had been made to the number of 21 news or 46.6% in Fajar and 24 news or 53.4% in Tribun Timur. When flooded disaster period, we can saw the role of print mass media by the story that they brought, Fajar brought 97 news or 75,8%, and Tribun Timur brought 31 news or 24,2%. For post flooded disaster period Fajar brought 14 news or 60,9%, and Tribun Timur brought nine news or 39,1%. It is concluded that local print media had a role for flooded disaster mitigation in society through their report that they brought. Hopefully, that people in the community would realize the danger of flooded disaster and taking care of nature.